Storytelling and English vocabulary learning among eighth-grade students at a public institution in Loja, during the 2022-2023 school year. - Sarmiento Granda, Carmen Esperanza (2023)
The main purpose of this study was to improve the learning of English language vocabulary by using storytelling among eighth-grade students at a public institution in Loja, during the 2022-2023 school year. Twenty-nine eighth grade students participated in the research. The researcher employed a mixed methodology to collect the necessary data. Quantitative data were obtained through a pre-test and post-test to assess students' vocabulary knowledge, while qualitative data were collected through a questionnaire and field notes to obtain students' perceptions. The data collected were analyzed using statistical formulas and presented in tables and graphs, along with a thematic analysis presented in narrative form. The results revealed a significant difference between the vocabulary level before and after implementing the narrative strategy. In addition, an improvement was observed in all three aspects of vocabulary: form, meaning, and use. In addition, students demonstrated motivation and interest in learning new words through the storytelling strategy, which also allowed them to develop their critical thinking. In conclusion, this study demonstrated that storytelling is a good strategy for learning English vocabulary because it offers a dynamic approach that encourages active participation, creativity, and word retention, captures students' attention, and stimulates their linguistic. Therefore, storytelling should be implemented into English vocabulary instruction as a strategy. Key words: Aspects of vocabulary, storytelling, vocabulary learning, types of stories.